2021
DOI: 10.1108/jic-01-2021-0039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of social capital on agribusiness diversification intention in the emerging market

Abstract: PurposeCoronavirus disease 2019 (COVID-19) has seriously affected the global economy. How agribusinessmen are overcoming this crisis is being noticed in emerging markets. Using social capital to diversify agribusiness for getting more customers is a useful solution for the growth of agribusiness. However, there is a lack of evidence on the aggregate measurement scale of social capital and the influence of behavioral goals on the intention toward agribusiness diversification. Therefore, this study aims to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 100 publications
(198 reference statements)
1
18
0
1
Order By: Relevance
“…subjective norms, attitude and PBC) contends that behavioral intention is a key factor in predicting a specific behavior (Ajzen, 1991). Specifically, some scholars have recently found that these TPB determinants have positive effects on sustainability-oriented entrepreneurial behavioral intentions (Vuorio et al, 2018), social entrepreneurship intentions (Tan et al, 2021) and agribusiness diversification intentions (Lang et al, 2021a). Thus, we argue that if agricultural entrepreneurs' attitude toward sustainable development through organic farming practices is positive, they can also have SAE intention.…”
Section: Extended Theory Of Planned Behavior and Sae Intentionmentioning
confidence: 77%
See 3 more Smart Citations
“…subjective norms, attitude and PBC) contends that behavioral intention is a key factor in predicting a specific behavior (Ajzen, 1991). Specifically, some scholars have recently found that these TPB determinants have positive effects on sustainability-oriented entrepreneurial behavioral intentions (Vuorio et al, 2018), social entrepreneurship intentions (Tan et al, 2021) and agribusiness diversification intentions (Lang et al, 2021a). Thus, we argue that if agricultural entrepreneurs' attitude toward sustainable development through organic farming practices is positive, they can also have SAE intention.…”
Section: Extended Theory Of Planned Behavior and Sae Intentionmentioning
confidence: 77%
“…The literature shows the existence of most measurements of the constructs, except for the measure of SAE intentions. Nevertheless, the measurements will benefit from a mixedmethods research design due to different contexts (Lang et al, 2021a), in which the qualitative method provides a richer understanding (Creswell, 2002), while the quantitative approach brings rigorous tests of measurements and hypotheses (Srnka and Koeszegi, 2007). So, a deep understanding will come from a mixed-methods approach (Arora and Stoner, 2009;Lang et al, 2022).…”
Section: Mixed-methods Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…For redesigning work, it is advisable to incorporate work elements that have been extended through our analysis (section 5) and theoretical contribution (section 6). The application should consider how the HRD managers or other managers find themselves in manufacturing alone or clubbed with service orientation (Lang et al, 2021a(Lang et al, , 2021b. Further, collaborative HRD practices (Chen et al, 2021) must cater to work roles that are becoming complex (Lee and Lee, 2018).…”
Section: Practical Implicationsmentioning
confidence: 99%